Social Physique Anxiety in Female Adolescents at Bandung Middle School - Nidya Fildza Hadiani; Nur Oktavia Hidayati; Citra Windani Mambang Sari (University of Muhammadiyah Malang, 2021)
Background: Adolescence is a transition from childhood to adulthood, along with physical and emotional changes. One significant difference is physical appearance. Adolescents tend to be afraid of negative evaluations from others for their physical appearance or social physique anxiety. Objective: This study aimed to determine the social physique anxiety in female adolescents at Bandung Middle School. Methods: This study's method was a descriptive quantitative method using a total population technique with a sample of 331 female high school students in Bandung Middle School. The measurement instrument that was used in this study was SPAS-C (Social Physique Anxiety for Children). Analysis of the data was conducted using the average score of social physique anxiety and was presented as a percentage. Result: This study showed that most respondents had a lower score than social physique anxiety average score with a several 176 respondents (53.2%), in comparison 155 respondents (46.8%) had a higher score than social physique anxiety average score. Based on the study results, comparing the number of respondents who had a lower score than the social physique anxiety average score with the number of respondents who had a higher score than the social physique anxiety average score did not significantly differ. Conclusions: Preventive solutions for social physique prevention are essential. Schools can make a consultation schedule or use an online consultation system and work with community health centers to provide health education and knowledge about social physique anxiety and the influencing factors and its prevention.